Made in Russia? Assessing Russia's potential for import substitution - Heli Simola (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2022)
Russia's brutal military aggression on Ukraine has led to extensive economic sanctions by Western countries and the withdrawal of many foreign companies from Russian markets. The isolation of Russia from the international community has substantially restricted its access to advanced technologies and eroded the country's economic growth potential. Our analysis suggests that Russia has fairly limited possibilities for import substitution in high-technology sectors. China, which could play a key role as an alternative source for inputs, has seen its share of Russian imports, including high-tech inputs, increase substantially in recent years. The extent to which China is willing to support Russia in the current situation remains unclear, however.
urn:nbn:fi:bof-202205051182
Keywords: 330; Russia; trade; sanctions; import substitution